Prevalence of Lipohypertrophy and Lipoatrophy in Individuals with Type 2 Diabetes and Determination of Associated Risk Factors - Kırmızıgül, Huriye; Şentürk, Seher Gönen (UI Scholars Hub, 2024)
Background: This study aimed to determine the prevalence of lipohypertrophy and lipoatrophy and their associated risk factors in individuals with type 2 diabetes taking insulin. Methods: This descriptive and cross-sectional study used the STROBE checklist. In January 2022 to April 2022, 271 individuals with type 2 diabetes were studied. The presence of lipoatrophy and lipohypertrophy was evaluated with inspection and palpation, and the sociodemographic and clinical characteristics of the patients were obtained using a questionnaire. Data were collected in face-to-face interviews. Results: Lipoatrophy and lipohypertrophy prevalence was 4.8% and 19.2%, respectively. Lipoatrophy was more common in patients who did not perform regular intra-regional rotation, and lipohypertrophy in those aged ≤60 years, women, those using insulin at a dose of >50 IU, those administering four injections per day, those using prandial and basal insulin, and those who did not perform regular systematic and intra-regional rotation (p < 0.05). Conclusions: Lipoatrophy and lipohypertrophy are common in patients with type 2 diabetes mellitus taking insulin and may develop due to some modifiable risk factors.